2015
DOI: 10.1089/neu.2014.3668
|View full text |Cite
|
Sign up to set email alerts
|

Expansion Duroplasty Improves Intraspinal Pressure, Spinal Cord Perfusion Pressure, and Vascular Pressure Reactivity Index in Patients with Traumatic Spinal Cord Injury: Injured Spinal Cord Pressure Evaluation Study

Abstract: We recently showed that, after traumatic spinal cord injury (TSCI), laminectomy does not improve intraspinal pressure (ISP), spinal cord perfusion pressure (SCPP), or the vascular pressure reactivity index (sPRx) at the injury site sufficiently because of dural compression. This is an open label, prospective trial comparing combined bony and dural decompression versus laminectomy. Twenty-one patients with acute severe TSCI had re-alignment of the fracture and surgical fixation; 11 had laminectomy alone (lamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
106
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(108 citation statements)
references
References 27 publications
1
106
1
Order By: Relevance
“…Therefore, not only hypoperfusion (SCPP below 90 mmHg), but also hyperperfusion (SCPP above 100 mmHg) may be detrimental for the injured spinal cord. This is consistent with our earlier report of a U-shaped relationship between the spinal pressure reactivity index and SCPP, which also indicated optimum SCPP around 90 mmHg 5,8,21 . After TSCI, ISP is 20 -30 mmHg and therefore SCPP 90 -100 mmHg corresponds to mean arterial pressure 110 -130 mmHg.…”
Section: Annals Of Neurologysupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, not only hypoperfusion (SCPP below 90 mmHg), but also hyperperfusion (SCPP above 100 mmHg) may be detrimental for the injured spinal cord. This is consistent with our earlier report of a U-shaped relationship between the spinal pressure reactivity index and SCPP, which also indicated optimum SCPP around 90 mmHg 5,8,21 . After TSCI, ISP is 20 -30 mmHg and therefore SCPP 90 -100 mmHg corresponds to mean arterial pressure 110 -130 mmHg.…”
Section: Annals Of Neurologysupporting
confidence: 93%
“…We also showed that simultaneous monitoring of SCPP and microdialysis could be used to enhance drug entry at the injury site. Based on our current findings and earlier studies [4][5][6][7][8][9]20,21 , a large-scale study of outcome from TSCI in patients who have monitoring vs. those who do not is warranted.…”
Section: Annals Of Neurologymentioning
confidence: 62%
See 1 more Smart Citation
“…26 Our data showed that in addition to bony decompression, expansion duraplasty was also required to effectively reduce ISP, increase SCPP, and improve the pressure reactivity at the injury site. 20 Laminectomy with duraplasty after TSCI is analogous to decompressive craniectomy after TBI, which involves not only bony but also dural decompression. The dura is a major, but unappreciated, cause of spinal cord compression after TSCI 18 and may explain why the benefits of early bony decompression (without opening the dura) after TSCI remain controversial.…”
mentioning
confidence: 99%
“…It has long been recognized in the experimental setting that perfusion of the spinal cord is highly associated with outcome 16, 17, 18. Recent human and veterinary studies have furthered our understanding of the role of spinal cord perfusion and hemodynamic changes, as well as the benefits of taking appropriate measures to maintain optimal spinal cord blood flow 19, 20, 21, 22, 23. Spinal cord perfusion is dependent on the relationship between systemic blood pressure and intrathecal pressure, in the same way that cerebral perfusion pressure is defined by mean arterial blood pressure (MABP) and intracranial pressure 17, 19, 24.…”
mentioning
confidence: 99%